High-performance wear-resistant ceramic material and preparation process thereof

By adjusting the proportion of mineral raw materials and introducing antibacterial agents and sintering additives, and using rare earth metal oxides and silver phosphate coating technology, the problem of insufficient wear resistance and antibacterial properties of sanitary ceramic materials is solved, and the wear resistance of ceramic materials is significantly improved and antibacterial properties, extend service life and improve gloss and density of glaze layer.

CN119306397APending Publication Date: 2025-01-14KAIPING GOLD MEDAL SHAITARY WARE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411437465.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The wear resistance of existing sanitary ceramic materials is poor, resulting in a decrease in gloss and a lighter color, which seriously shortens the service life. The glaze layer is prone to form pores during firing, affecting smoothness.

Method used

By adjusting the proportion of mineral raw materials, introducing antibacterial agents and sintering aids, using rare earth metal oxides to refine grains, increasing density, and improving the dispersion and stability of antibacterial agents through the coating technology of silver phosphate and alumina sol, The cordierite phase is formed to improve wear resistance.

Benefits of technology

It significantly improves the wear resistance and antibacterial properties of ceramic materials, improves the gloss and density of the glaze layer, extends the service life, and enhances the antibacterial stability, avoiding the burning of antibacterial agents caused by high-temperature firing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005085438180000071
    Figure BDA0005085438180000071
Patent Text Reader

Abstract

The invention discloses a high-performance wear-resistant ceramic material and a preparation process thereof, and belongs to the technical field of ceramics, the ceramic material comprises a green body and a glaze surface, the glaze surface is obtained by firing a glaze material on the surface of the green body, and the glaze material comprises a mineral raw material, an antibacterial agent, a dispersing agent and a sintering aid; the mineral raw materials comprise the following raw materials in parts by weight: 25-30 parts of quartz, 1.5-2 parts of zinc oxide, 7-8 parts of zirconium silicate, 23-28 parts of potassium feldspar, 7-9 parts of calcite, 3-5 parts of dolomite, 14-15 parts of wollastonite, 5-8 parts of calcined kaolin, 3-5 parts of 809 frit and 3-5 parts of calcined talc; the sintering aid is a rare earth metal oxide, and the antibacterial agent is a silver antibacterial agent; by optimizing the formula, rare earth metal oxide is introduced as a sintering aid to refine crystal grains, the compactness of a glaze layer is improved, the ceramic material is endowed with antibacterial performance by introducing an antibacterial agent, and the wear resistance of the sanitary ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramics, and in particular relates to a high-performance wear-resistant ceramic material and a preparation process thereof. Background Art

[0002] Sanitary ceramics are glazed ceramic products used in bathrooms, kitchens, laboratories and other places, also known as sanitary ware. However, unlike decorative porcelain, sanitary ceramics are often washed and worn during use, and aging is more obvious, causing the gloss of sanitary ceramics to decrease and the color to fade, which seriously shortens the service life of sanitary ceramics. The quality of sanitary ceramics is most critical to the glaze layer, and the composition of the glaze has a great influence on the performance of the glaze layer. Therefore, it is very important to improve the wear resistance of sanitary ceramics by improving the ceramic glaze.

[0003] The patent application with publication number CN113185126A discloses a highly wear-resistant sanitary ceramic and a preparation method thereof, the sanitary ceramic comprises a body and a glaze layer; the glaze of the glaze layer comprises the following components by weight: 27-32 parts of quartz, 23-28 parts of potassium feldspar, 3-5 parts of zinc oxide, 12-15 parts of calcite, 7-8 parts of dolomite, 7-9 parts of zirconium silicate, 1.5-2.5 parts of aluminum oxide, 5-7 parts of Suzhou soil, 2.5-3.5 parts of frit, and 10-15 parts of modified pyrophyllite powder. The calcite and dolomite in the formula cooperate with each other to effectively promote the dissolution of quartz and the formation of mullite crystals; zinc oxide can also play a role of fluxing, and when used in combination with calcite and dolomite, it can effectively improve the glossiness and wear resistance of the glaze layer. However, the formula contains a lot of dolomite and calcite, which decompose during the firing process and emit carbon dioxide gas. During the cooling process of the glaze, the gas solidifies on the surface of the glaze to form pores, making the glaze not smooth enough. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance wear-resistant ceramic material and a preparation process thereof, so as to solve the problem of poor wear resistance of ceramic materials.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-performance wear-resistant ceramic material comprises a body and a glaze, wherein the glaze is obtained by firing a glaze on the surface of the body, wherein the glaze comprises mineral raw materials, an antibacterial agent, a dispersant and a sintering aid; the mineral raw materials comprise the following raw materials in parts by weight: 25-30 parts of quartz, 1.5-2 parts of zinc oxide, 7-8 parts of zirconium silicate, 23-28 parts of potassium feldspar, 7-9 parts of calcite, 3-5 parts of dolomite, 14-15 parts of wollastonite, 5-8 parts of calcined kaolin, 3-5 parts of 809 frit and 3-5 parts of calcined talc; in order to improve the performance of the ceramic material, a small proportion of calcite and dolomite are added in the present invention, and the wear resistance of the glaze is improved by introducing the antibacterial agent and the sintering aid.

[0007] The sintering aid is a rare earth metal oxide; the amount of the rare earth metal oxide is 2%-4% of the weight of the mineral raw material;

[0008] The amount of the dispersant is 0.2%-0.3% by weight of the mineral raw material;

[0009] The antibacterial agent is a silver-based antibacterial agent, and the added amount of the antibacterial agent is 8%-10% of the weight of the mineral raw material.

[0010] As a further preferred embodiment of the present invention, the dispersant is carboxymethyl cellulose.

[0011] As a further preferred embodiment of the present invention, the rare earth metal oxide is one of yttrium oxide and lanthanum oxide.

[0012] As a further preferred embodiment of the present invention, the antibacterial agent is prepared by the following steps:

[0013] Silver phosphate is added to alumina sol and stirred and mixed, and vacuum dried at 60°C to constant weight to obtain an antibacterial agent. The antibacterial agent forms a gel film on the surface of the silver phosphate, and then undergoes high-temperature sintering, which is equivalent to coating the surface of the silver phosphate with a gel layer.

[0014] As a further preferred embodiment of the present invention, the mass ratio of silver phosphate to alumina sol is 1:4-5.

[0015] As a further preferred embodiment of the present invention, the alumina sol is prepared by the following steps:

[0016] Aluminum isopropoxide and water are mixed, hydrolyzed for 3-4 hours, nitric acid is added to adjust the system to a weakly acidic pH value of 4-5, and after stirring and dispersing, the system is aged at 90° C. to obtain an alumina sol.

[0017] As a further preferred embodiment of the present invention, the usage ratio of aluminum isopropoxide and water is 1 g:20 mL.

[0018] A preparation process of a high-performance wear-resistant ceramic material comprises the following steps:

[0019] The first step is to weigh various raw materials according to the composition of the glaze, perform ball milling, sieve and remove iron after ball milling to obtain the glaze;

[0020] The second step is to apply the glaze on the surface of the sanitary ceramic body with a thickness of 0.8-1.2 mm, and then burn it after drying to obtain a high-performance wear-resistant ceramic material.

[0021] As a further preferred embodiment of the present invention, during ball milling, the ratio of material: ball: water is 1:2:0.8, and after ball milling, the material is sieved through a 200-mesh sieve.

[0022] As a further preferred solution of the present invention, it is characterized in that the firing temperature is 1280-1300°C.

[0023] Beneficial effects of the present invention:

[0024] The present invention prepares a high-performance wear-resistant ceramic material. The wear resistance of the ceramic material is improved by adjusting the ratio of mineral raw materials, antibacterial agents, dispersants and sintering aids, optimizing the formula, and introducing rare earth metal oxides as sintering aids to refine grains and increase the density of the glaze layer, thereby further improving the wear resistance of sanitary ceramics; and the antibacterial agent is introduced to give the ceramic material antibacterial properties.

[0025] In order to further improve the antibacterial properties of the wear-resistant material, a homemade antibacterial agent is added to the raw materials of the ceramic material of the present invention. The antibacterial agent is obtained by mixing silver phosphate and alumina sol and then drying them. After coating, the problem of poor dispersibility of silver phosphate can be solved. On the other hand, after coating with alumina sol, the bonding strength of the silver phosphate interface can be improved, and a cordierite phase can be formed in situ under the promotion of rare earth metal oxides. In addition, the stability of the antibacterial agent is poor during high-temperature firing. The protective layer formed on the surface of silver phosphate can improve the problem of easy burning and improve the antibacterial stability of the antibacterial agent. The alumina sol participates in the formation of a glass network with silicon dioxide (derived from ore raw materials) during the sintering process, making the glaze structure dense, thereby improving the wear resistance of the glaze. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The chemical compositions of the mineral raw materials used in the examples and comparative examples are shown in Table 1 below:

[0028] Table 1

[0029] Raw material name <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> ZnO <![CDATA[ZrO2]]> BaO IL quartz 100 0-3 Zinc Oxide 100 0-2 Zirconium silicate 28-32 70 0-3 Potassium feldspar 62-69 13-17 0-0.3 0-1 0-1 7.5-12.5 2-5 0-1 Calcite 0.15 48 42 dolomite 32 20-26 42-48 Wollastonite 52 42-48 0-5 Calcined Kaolin 50-55 38-44 0-0.5 0-1 0-1 0-2 0-1 0-1 809 Frit 65 16 0.15 8-10 1-2 2-4 1-2 7-10 0-2 0-1 Burnt Talc 60-65 0-0.3 30-38 0-3

[0030] Antimicrobial agent: Homemade.

[0031] Preparation Example 1

[0032] Preparation of antimicrobial agent:

[0033] 15 g of aluminum isopropoxide and 300 mL of water were mixed and hydrolyzed for 3 h. Nitric acid was added to adjust the system to a weakly acidic pH value of 4-5. After stirring and dispersing, the mixture was aged at 90° C. for 10 h to obtain an alumina sol.

[0034] Silver phosphate was added to the alumina sol, stirred and mixed, and vacuum dried at 60°C to a constant weight to obtain an antibacterial agent. The mass ratio of silver phosphate to alumina sol was 1:4.

[0035] Preparation Example 2

[0036] Preparation of antimicrobial agent:

[0037] 15 g of aluminum isopropoxide and 300 mL of water were mixed and hydrolyzed for 3 h. Nitric acid was added to adjust the system to a weakly acidic pH value of 4-5. After stirring and dispersing, the mixture was aged at 90° C. for 10 h to obtain an alumina sol.

[0038] Silver phosphate was added to the alumina sol, stirred and mixed, and vacuum dried at 60°C to a constant weight to obtain an antibacterial agent. The mass ratio of silver phosphate to alumina sol was 1:5.

[0039] Example 1-Example 3

[0040] Provided is a high-performance wear-resistant ceramic material, comprising a body and a glaze, wherein the glaze is obtained by firing a glaze on the surface of the body, wherein the glaze comprises a mineral raw material, an antibacterial agent prepared in Preparation Example 1-Preparation Example 2, carboxymethyl cellulose and yttrium oxide (rare earth metal oxide); the mineral raw material comprises the following raw materials in parts by weight: 25-30 parts of quartz, 1.5-2 parts of zinc oxide, 7-8 parts of zirconium silicate, 23-28 parts of potassium feldspar, 7-9 parts of calcite, 3-5 parts of dolomite, 14-15 parts of wollastonite, 5-8 parts of calcined kaolin, 3-5 parts of 809 frit and 3-5 parts of burned talc;

[0041] Referring to the ratios in Table 2, the test samples were prepared by adjusting the ratios of the mineral raw materials in Examples 1 to 3.

[0042] Table 2

[0043] Raw material name Example 1 Example 2 Example 3 quartz 25 28 30 Zinc Oxide 1.5 1.5 1.5 Alumina 1.5 1.5 1.5 Zirconium silicate 8 7 7 Potassium feldspar 28 24 23 Calcite 7 8 9 dolomite 5 4 3 Wollastonite 14 14 15 Calcined Kaolin 5 8 6 809 Frit 3 4 5 Burnt Talc 5 4 3

[0044] The amount of dilute yttrium oxide used is 2% by weight of the mineral raw material;

[0045] The amount of carboxymethyl cellulose used is 0.2% by weight of the mineral raw material;

[0046] The amount of antibacterial agent added is 8% by weight of the mineral raw material.

[0047] The preparation process of the high-performance wear-resistant ceramic material comprises the following steps:

[0048] Step 1: Weigh various raw materials according to the composition of the glaze, and use a planetary ball mill to mill for 90 minutes at a speed of 380r / min according to the ratio of material: ball: water = 1:2:0.8. After ball milling, pass through a 200-mesh standard sieve and remove iron to obtain the glaze;

[0049] The second step is to apply the glaze on the surface of the body with a glaze layer thickness of 0.8-1.2mm; first place it in a drying room at 50℃ for 18-24h, and then place it in a kiln for firing at a firing temperature of 1280-1300℃. After firing, a high-performance wear-resistant ceramic material is obtained.

[0050] Example 4

[0051] Compared with Example 1, the amount of rare earth metal oxide in Example 1 is adjusted to 3% of the weight of the mineral raw material, and the other raw materials and preparation process remain the same as those in Example 1.

[0052] Example 5

[0053] Compared with Example 1, the amount of rare earth metal oxide in Example 1 is adjusted to 4% of the weight of the mineral raw material, and the other raw materials and preparation process remain the same as those in Example 1.

[0054] Example 6

[0055] Compared with Example 1, the rare earth metal oxide in Example 1 is replaced by lanthanum oxide in this example, and the other raw materials and preparation process remain the same as those in Example 1.

[0056] Example 7

[0057] Compared with Example 1, the addition amount of the antibacterial agent in this example is 10% of the weight of the mineral raw material, and the other raw materials and preparation process remain the same as those in Example 1.

[0058] Example 8

[0059] Compared with Example 1, the antibacterial agent in this example is replaced by the antibacterial agent prepared in Preparation Example 2, and the other raw materials and preparation process remain the same as those in Example 1.

[0060] Comparative Example 1

[0061] Compared with Example 1, the antibacterial agent in this comparative example is replaced with silver phosphate, and the amount of the antibacterial agent is adjusted to 1.5% of the weight of the mineral raw material. The other raw materials and preparation process remain the same as those in Example 1.

[0062] Comparative Example 2

[0063] Compared with Example 1, the rare earth metal oxide in this comparative example is replaced by zinc oxide, and the other raw materials and preparation process remain the same as those in Example 1.

[0064] Comparative Example 3

[0065] Compared with Comparative Example 1, the rare earth metal oxide in this comparative example is replaced by zinc oxide, and the other raw materials and preparation process remain the same as those in Comparative Example 1.

[0066] Comparative Example 4

[0067] Compared with Example 1, the dosage of the rare earth metal oxide in this comparative example is increased to 5%, and the other raw materials and preparation process remain the same as those in Example 1.

[0068] Performance tests were performed on Examples 1 to 8 and Comparative Examples 1 to 3. The wear resistance of the samples was tested according to standard GB / T3810.7-2016; the Mohs hardness of the samples was tested and recorded;

[0069] The antibacterial rate samples were tested using the international standard ISO22196-2011. The test strain was ATCC8739 Escherichia coli. Place a 5cmx5cm sample in a sterilized culture dish, use a pipette to measure 0.4mL of the cultured bacterial solution (Escherichia coli) to the surface of the sample, and cover it with a film. Culture it for 24 hours at a temperature of (35±1)℃ and a humidity of not less than 90%. Record the arithmetic mean of the number of live bacteria on the surface of the sample after 24 hours, and calculate the antibacterial rate of the sample. The test results are shown in Table 3:

[0070] Table 3

[0071]

[0072]

[0073] It can be seen from Table 3 that the wear resistance and antibacterial properties prepared by the present invention, according to the data comparison of Example 1 and Comparative Examples 1-3, replacing the antibacterial agent with silver phosphate leads to an increase in the wear value of the sample, and replacing the rare earth metal oxide with zinc oxide (zinc oxide can also be used as a sintering aid) also leads to an increase in the wear value. Therefore, the addition of rare earth metal oxides and antibacterial agents is beneficial to enhancing the wear resistance of the sample, and there is a certain synergistic effect between the two. In the present invention, the sintering aid is a rare earth metal oxide, which can refine the grains, fill the grain gaps, improve the density of the sample, and increase the hardness of the sample, but the amount of rare earth metal oxide should not be too much. Too much rare earth metal oxide will cause the grain size to be too large, which is not conducive to the improvement of density and affects the wear resistance of the sample.

[0074] In the present invention, the silver phosphate coated with alumina sol has good dispersibility and forms a protective layer on the surface of the silver phosphate, so the glaze in the present invention can still maintain strong antibacterial properties after high-temperature sintering. In addition, after the alumina sol is coated and then sintered, a cordierite phase can be formed under the condition of high-temperature firing under the promotion of rare earth metal oxides. The cordierite phase is beneficial to improving the wear resistance of the glaze layer. In addition, the stability of the antibacterial agent after high-temperature sintering is also significantly improved. At the same time, it can also avoid the problem that the stability of the antibacterial agent is affected by excessively high temperatures during processing, resulting in a decrease in antibacterial performance. In addition, rare earth metals are natural and excellent antibacterial materials, and they also have good synergistic effects with silver-based antibacterial agents.

[0075] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-performance wear-resistant ceramic material, comprising a body and a glaze, characterized in that: The glaze surface is obtained by firing the glaze on the surface of the body, and the glaze includes mineral raw materials, antibacterial agents, dispersants and sintering aids; the mineral raw materials include the following raw materials by weight: 25-30 parts of quartz, 1.5-2 parts of zinc oxide, 7-8 parts of zirconium silicate, 23-28 parts of potassium feldspar, 7-9 parts of calcite, 3-5 parts of dolomite, 14-15 parts of wollastonite, 5-8 parts of calcined kaolin, 3-5 parts of 809 frit and 3-5 parts of burned talc; The sintering aid is a rare earth metal oxide; the amount of the rare earth metal oxide is 2%-4% of the weight of the mineral raw material; The amount of the dispersant is 0.2%-0.3% by weight of the mineral raw material; The antibacterial agent is a silver-based antibacterial agent, and the added amount of the antibacterial agent is 8%-10% of the weight of the mineral raw material.

2. A high performance wear-resistant ceramic material according to claim 1, characterized in that: The dispersant is carboxymethyl cellulose.

3. A high performance wear-resistant ceramic material according to claim 1, characterized in that: The rare earth metal oxide is one of yttrium oxide and lanthanum oxide.

4. A high performance wear-resistant ceramic material according to claim 1, characterized in that: The antibacterial agent is prepared by the following steps: Silver phosphate was added into the alumina sol, stirred and mixed, and vacuum dried at 60° C. to a constant weight to obtain an antibacterial agent.

5. A high performance wear-resistant ceramic material according to claim 4, characterized in that: The mass ratio of silver phosphate to alumina sol is 1:4-5.

6. A high performance wear-resistant ceramic material according to claim 4, characterized in that: The alumina sol is prepared by the following steps: Aluminum isopropoxide and water are mixed, hydrolyzed for 3-4 hours, nitric acid is added to adjust the system to a weakly acidic pH value of 4-5, and after stirring and dispersing, the system is aged at 90° C. to obtain an alumina sol.

7. A high performance wear-resistant ceramic material according to claim 1, characterized in that: The dosage ratio of aluminum isopropoxide and water is 1 g:20 mL.

8. A process for preparing a high performance wear-resistant ceramic material according to any one of claims 1 to 7, characterized in that: The steps include: The first step is to weigh various raw materials according to the composition of the glaze, perform ball milling, sieve and remove iron after ball milling to obtain the glaze; The second step is to apply the glaze on the surface of the sanitary ceramic body with a thickness of 0.8-1.2 mm, and then burn it after drying to obtain a high-performance wear-resistant ceramic material.

9. The process for preparing a high performance wear-resistant ceramic material according to claim 8, characterized in that: During ball milling, material: ball: water = 1:2:0.

8. After ball milling, pass through a 200-mesh sieve.

10. The process for preparing a high performance wear-resistant ceramic material according to claim 8, characterized in that: The firing temperature is 1280-1300℃.

Citation Information

Patent Citations

  • High-wear-resistance sanitary ceramic and preparation method thereof

    CN113185126A